2016
DOI: 10.1002/2015ja022082
|View full text |Cite
|
Sign up to set email alerts
|

Traveling planetary‐scale waves in the lower thermosphere: Effects on neutral density and composition during solar minimum conditions

Abstract: The effects of breaking of traveling, planetary scale Rossby waves (TPWs) in the lower thermosphere are investigated with respect to the mixing of neutral constituents. We use numerical simulations of the Whole Atmosphere Community Climate Model, eXtended version, whose meteorology below 92 km is constrained by atmospheric specifications obtained from operational weather forecast/data assimilation system. The Fourier spectra show that the amplitude of TPWs with periods between 3 and 10 days are statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 69 publications
(117 reference statements)
0
20
0
Order By: Relevance
“…And they are also similar in magnitude to the changes caused by tidal waves [e.g., Yamazaki and Richmond, 2013]. Recent numerical studies using WACCM-X by Sassi et al [2016] found that during periods of strong TPWs events (with periods between 3 and 10days), the dissipation of TPWs in the lower thermosphere reinforces the mean meridional circulation with stronger upwelling in the tropics and downwelling at high latitudes. This, along with fast molecular diffusion, reduces the O/N 2 and neutral density at high latitudes while slightly increasing these quantities at low latitudes.…”
Section: 1002/2016sw001450mentioning
confidence: 73%
See 1 more Smart Citation
“…And they are also similar in magnitude to the changes caused by tidal waves [e.g., Yamazaki and Richmond, 2013]. Recent numerical studies using WACCM-X by Sassi et al [2016] found that during periods of strong TPWs events (with periods between 3 and 10days), the dissipation of TPWs in the lower thermosphere reinforces the mean meridional circulation with stronger upwelling in the tropics and downwelling at high latitudes. This, along with fast molecular diffusion, reduces the O/N 2 and neutral density at high latitudes while slightly increasing these quantities at low latitudes.…”
Section: 1002/2016sw001450mentioning
confidence: 73%
“…TPWs in the winter hemisphere can propagate equatorward and break at subtropical surf zone in the lower thermosphere, as shown by Sassi et al []. In addition to causing mean flow acceleration, the wave breaking also results in a meridional, down‐gradient mixing of constituents.…”
Section: Upper Atmosphere Variability As Related To Tides and Other Pmentioning
confidence: 98%
“…The global zonal winds shown in Figure 4a typically range from 0 to 10 m/s eastward (i.e., superrotating); the large spike in January is the result of a sudden stratospheric warming. Figure 4b shows that the root variance of the zonal winds ranges from 0 to 25 m/s, with the lower values concentrated at high southern latitudes (compare with the greater traveling planetary wave activity in the Northern Hemisphere during this period reported by Sassi et al [2016]). Winds at this altitude are significant because the conductivity peaks near 100-120 km, allowing these winds to couple to the global wind-driven dynamo.…”
Section: Sami3/waccm-x Ionosphere/thermosphere Modelingmentioning
confidence: 84%
“…However, the impact of these changes on the ionosphere and upper thermosphere remains unclear. It is additionally unknown whether these changes are induced by the SW2 or by gravity wave [Miyoshi et al, 2015] or planetary wave [Sassi et al, 2016] variability during SSWs.…”
Section: Introductionmentioning
confidence: 99%